Management of Decongestion in Acute Heart Failure: Time for a New Approach? - Pramudyo, Miftah; Putra, Iwan Cahyo Santosa; Zulkarnain, Edrian; Danny, Siska Suridanda; Danny, Hendry Purnasidha; Anjarwani, Setyasih; Mazwar, Irmaliyas; Juzar, Dafsah Arifa; Pratama, Vireza; Habib, Faisal; Ispar, Akhtar Fajar Muzakkir Ali; Widyantoro, Bambang (The Indonesian Heart Association, 2025)
In “Management of Decongestion in Acute Heart Failure: Time for a New Approach?” (Indonesian Journal of Cardiology, 43(2), 77-89. https://doi.org/10.30701/ijc.1381), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1381. The error occurs only in the PDF; the DOI listed in the article metadata is already correct. The publisher apologizes for any inconvenience caused by this error.DOI of original article: https://doi.org/10.30701/ijc.1381